Climate, Thermal Coal and Carbon - Lilford, Eric (2020)
Pressure is mounting globally for the discontinuation of the use of thermal coal and other carbonbased fuels for power generation. The pressure to shift power-generating fuel sources to cleaner propositions comes from many fronts, including from financial institutions that have removed funding options for new and existing coal projects, large investment houses that have discontinued coal equity investments from their portfolios, social movements that have heightened awareness and have created industrial and societal disruptions and, notably, scientists and other researchers who have pronounced the need to reduce carbon-rich energy sources for environmental reasons. However, despite this, thermal coal continues to play an important role in power generation in many regions around the world and will continue to do so for decades to come. This is because coal is an abundant mineral, the power-conversion technology is tried and tested and, comparatively, coal power generation tends to be a more affordable option when considered against numerous alternatives. This latter point excludes the cost impacts associated with carbon taxes. This paper specifically covers the relationship between the amount of CO2 produced from the combustion of thermal coal for power generation purposes and the additional heating effect, measured in degrees Celsius, that this CO2 creates. It also provides explicit and comparative figures relating to the world’s largest thermal coal consumers and hence the largest contributors to climate change relating to the combustion of thermal coal.